2018
DOI: 10.1111/jnc.14483
|View full text |Cite
|
Sign up to set email alerts
|

Absence of infiltrating peripheral myeloid cells in the brains of mouse models of lysosomal storage disorders

Abstract: Approximately 70 lysosomal storage diseases are currently known, resulting from mutations in genes encoding lysosomal enzymes and membrane proteins. Defects in lysosomal enzymes that hydrolyze sphingolipids have been relatively well studied. Gaucher disease is caused by the loss of activity of glucocerebrosidase, leading to accumulation of glucosylceramide. Gaucher disease exhibits a number of subtypes, with types 2 and 3 showing significant neuropathology. Sandhoff disease results from the defective activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 80 publications
2
13
0
Order By: Relevance
“…Our study reveals pathological proteomic fingerprints of microglia in pre-symptomatic phase of NPC that associate with enhanced phagocytic uptake, increased synaptic pruning, impaired myelin turnover and its accumulation within MVBs. Microglia are responsible for the neuroinflammatory phenotype that occurs in brains of Npc1 -/mice as infiltration of peripheral macrophages could not be detected in this model (Cho, Vardi et al, 2018, Cougnoux et al, 2018. However, the contribution of microglial activation to neurodegeneration in NPC is still being discussed (Baudry et al, 2003, Gabande-Rodriguez et al, 2018, Lopez et al, 2011, Peake et al, 2011, Pressey et al, 2012.…”
Section: Discussionmentioning
confidence: 85%
“…Our study reveals pathological proteomic fingerprints of microglia in pre-symptomatic phase of NPC that associate with enhanced phagocytic uptake, increased synaptic pruning, impaired myelin turnover and its accumulation within MVBs. Microglia are responsible for the neuroinflammatory phenotype that occurs in brains of Npc1 -/mice as infiltration of peripheral macrophages could not be detected in this model (Cho, Vardi et al, 2018, Cougnoux et al, 2018. However, the contribution of microglial activation to neurodegeneration in NPC is still being discussed (Baudry et al, 2003, Gabande-Rodriguez et al, 2018, Lopez et al, 2011, Peake et al, 2011, Pressey et al, 2012.…”
Section: Discussionmentioning
confidence: 85%
“…Whether the myeloid cells that do not express TMEM119 or express it at low levels in ASMko brains are DAM, monocyte-derived "microglia-like" cells or both remains to be clarified. Very recent reports suggest the absence of monocyte infiltration in the brain of mouse models for LSDs including NPC (Cho et al, 2018;Cougnoux et al, 2018). These findings would support that the TMEM119negative cells are DAM.…”
Section: Discussionmentioning
confidence: 99%
“…The authors focused on three LSDs where strong evidence of cytokine/chemokine expression in the brain exists; namely, neuropathic Gaucher disease, Sandhoff disease, and Niemann Pick type C. Using a flow cytometry‐based approach, where microglia were discriminated from infiltrating myeloid cells on the basis of differential CD45 expression, Cho et al . () found no evidence of peripheral myeloid influx in any of the three mouse LSD models examined. This raises the possibility that resident microglia likely contribute to neurodegenerative processes and reactive microglia have been demonstrated in almost all LSDs affecting the CNS.…”
mentioning
confidence: 85%
“…in this Special Issue addresses an ongoing debate as to whether select LSDs are associated with an influx of peripheral myeloid cells into the brain, which would be expected to contribute to the neurodegenerative process (Cho et al . ). Although prior work had suggested that peripheral myeloid cells infiltrate the CNS following bone marrow transfer, this involves irradiation that is known to compromise blood–brain barrier integrity.…”
mentioning
confidence: 97%
See 1 more Smart Citation